Selecting an optimal ground support system for rockbursting conditions - Louchnikov, V; Sandy, MP (Deep Mining 2017: Eighth International Conference on Deep and High Stress Mining, 2017)
A growing number of underground mines experience high seismic activity due to the expansion of the mined out void and the progressive advancement of the operations to greater depths. Seismic events with a local magnitude ranging from 1.5 to 3.0 are routinely recorded at various mines in Western Australia where many such events have resulted in rockbursts damaging underground excavations and posing a high risk of injury to underground workers. Being the last line of defence in mitigating the risk of a rockburst occurrence, an optimal ground support system must be sufficiently robust to survive the highest magnitude event predicted by seismological analysis, yet still be economically and practicably feasible to ensure sustainability of the mining operation. This paper presents the process of ground support selection as applied to two Western Australian hard rock mines experiencing rockbursting conditions. The methodology is presented in the format of the capacity meeting the demand. Various commercially available rockbolts and surface liners are reviewed in terms of their energy absorption and deformation capacities. Once all data on the demand and capacity is in hand, the task of selecting an optimal support is then a matter of ranking the systems, shortlisting the better ones for a trial, and finally deciding on the most optimal one or two.
Keywords: rockburst; dynamic ground support; optimisation